Therapeutic Potential of Mesenchymal Stem Cells and Their Secretome in Ameliorating Renal Fibrosis: A Comprehensive Narrative Review - Amansyah, Fajar; Amalina, Nur Dina (International Journal of Cell and Biomedical Science, 2024)
Chronic kidney disease (CKD) represents a global health challenge with limited therapeutic options, often progressing to end-stage renal disease requiring dialysis or transplantation. Renal fibrosis, characterized by excessive extracellular matrix deposition and loss of functional nephrons, constitutes the final common pathway for most progressive kidney diseases. Conventional therapies primarily target symptoms rather than underlying pathological mechanisms. Mesenchymal stem cells (MSCs) have emerged as promising candidates for regenerative therapy due to their multipotent differentiation capabilities, immunomodulatory properties, and paracrine effects. Growing evidence suggests that the therapeutic benefits of MSCs are predominantly mediated through their secretome—a complex mixture of soluble factors, extracellular vesicles, and exosomes. This narrative review comprehensively examines the current understanding of MSC-based therapies for renal fibrosis, with particular emphasis on their secretome. We explore the mechanisms of action, preclinical evidence, ongoing clinical trials, and challenges in translating MSC secretome-based therapies to clinical applications. Recent advances in secretome characterization, bioengineering approaches to enhance therapeutic efficacy, and targeted delivery strategies are also discussed. Despite promising results, several hurdles remain, including standardization of preparation protocols, identification of key therapeutic components, and optimization of delivery methods. This review highlights the transformative potential of MSC secretome in renal fibrosis treatment while acknowledging the need for further research to realize its full clinical potential.